Fire Fighting Robot with Receiver and Transmitter System (AI Integrated) (International Journal of Scientific Research in Science and Technology, 2025)
Fire accidents pose a major threat to life and property, often occurring in locations that are too dangerous for human firefighters to access. The advancement of robotics and automation provides an effective solution to mitigate such risks. This project focuses on designing and developing an Arduino-based fire-fighting robot capable of detecting and extinguishing small fires autonomously. This project is based on the design of a low-cost, semi-autonomous robot that can find a fire source with its sensors and pump water to extinguish it. The robot tries to minimize the involvement of human beings in hazardous environments, providing an efficient, reliable, and prompt response system against all sorts of incidents related to fire, especially within small or confined areas. an outcome of the work, a fully functional prototype should be expected which will locate the source of fire independently and extinguish it effectively. The system will improve safety and reduce human risk while validating the potential in low-cost robotics solutions for emergency response applications.